Juridical Review Of The Prevention and Action Of Pornography in The Virtual World - Erwin Taroreh; Dandy Adityah Syafaat (LEGAL BRIEF, 2022)
The purpose of this research is to study how Indonesian laws and regulations regulate the prevention and prosecution of pornography crimes in cyberspace. This research uses a normative approach to legal research or library research, namely legal research conducted by looking at library materials. This legal research uses data on primary and secondary legal materials. Primary legal materials are laws and regulations, while secondary legal materials include journals, theses and other works. The inductive method is used to analyze data to produce recommendations or suggestions. This research shows that the Indonesian Pornography Law, the Minister of Communication and Informatics Law, the Criminal Code, the Information and Electronic Transactions Law, the Film Law, the Press Law, the Broadcasting Law, and the Telecommunications Law all clearly cover the prevention and prosecution of pornography crimes